Representasi Inner Child pada Tokoh Utama Taeko Okajima dalam Film Animasi Omohide Poroporo Karya Isao Takahata - Riztanti Ayu Maulidha (ICHIGO : Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2024)
Animated film’s Omohide Poroporo has two objectives. The first is to explain the fictional structure in the animated film Omohide Poroporo by Isao Takahata. The second is representation of inner child in the main character Taeko Okajima. The research of animated film’s uses scenes and conversational dialouge from the characters in the animated film Omohide Poroporo as a data source and a descriptive qualitative research method using theory building. Based on the result on the animated film’s Omohide Poroporo by Isao Takahata, it was found that internal trauma is caused by childhood trauma and has an impact in adulthood. Isao Takahata throught the animated film Omohide Poroporo provides recommendations for viewers regarding the importance of mental health, especially trauma in childhood. This indicates that films as literary products are a promotional medium so that people care more about children’s mental conditions.